Analisis Implementasi Fungsi Pengorganisasian dalam Manajemen Talenta Perusahaan Startup Teknologi di Jakarta pada Era Transformasi Digital - Natasya Natasya; Kholilul Kholik; Sekar Ningrum; Khansa Nada Syifa; Yuli Najiha Fitria; Afrida Amelia; Bagas Ranzie Fahlepy (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
Digital transformation has significantly changed organizational management practices, particularly in technology Startup companies operating in Jakarta. Startups are required to adopt adaptive and flexible organizational structures to support rapid innovation and maintain competitiveness in the digital era. In this context, the organizing function plays a strategic role as it serves as the foundation for task distribution, authority delegation, and coordination among individuals and work teams. This article aims to analyze the implementation of the organizing function in talent management within technology Startup companies in Jakarta during the digital transformation era. This study employs a qualitative approach using a literature review method, analyzing national and international journal articles, academic books, and relevant scientific publications related to organizing functions, talent management, and digital transformation. The findings indicate that technology Startups tend to implement flat organizational structures and cross-functional teams to enhance collaboration and operational efficiency. However, such flexibility also presents challenges, including role ambiguity and weak coordination if not supported by systematic organizing practices. Therefore, integrating organizing functions with strategic talent management is essential to support digital transformation and ensure sustainable organizational performance in technology Startups.